Drug‐like sphingolipid SH‐BC‐893 opposes ceramide‐induced mitochondrial fission and corrects diet‐induced obesity. Issue 8 (7th July 2021) - Jayashankar, Vaishali; Selwan, Elizabeth; Hancock, Sarah E; Verlande, Amandine; Goodson, Maggie O; Eckenstein, Kazumi H; Milinkeviciute, Giedre; Hoover, Brianna M; Chen, Bin; Fleischman, Angela G; Cramer, Karina S; Hanessian, Stephen; et al.
Abstract: Ceramide‐induced mitochondrial fission drives high‐fat diet (HFD)‐induced obesity. However, molecules targeting mitochondrial dynamics have shown limited benefits in murine obesity models. Here, we reveal that these compounds are either unable to block ceramide‐induced mitochondrial fission or require extended incubation periods to be effective. In contrast, targeting endolysosomal trafficking events important for mitochondrial fission rapidly and robustly prevented ceramide‐induced disruptions in mitochondrial form and function. By simultaneously inhibiting ARF6‐ and PIKfyve‐dependent trafficking events, the synthetic sphingolipid SH‐BC‐893 blocked palmitate‐ and ceramide‐induced mitochondrial fission, preserved mitochondrial function, and prevented ER stress in vitro. Similar benefits were observed in the tissues of HFD‐fed mice. Within 4 h of oral administration, SH‐BC‐893 normalized mitochondrial morphology in the livers and brains of HFD‐fed mice, improved mitochondrial function in white adipose tissue, and corrected aberrant plasma leptin and adiponectin levels. As an interventional agent, SH‐BC‐893 restored normal body weight, glucose disposal, and hepatic lipid levels in mice consuming a HFD. In sum, the sphingolipid analog SH‐BC‐893 robustly and acutely blocks ceramide‐induced mitochondrial dysfunction, correcting diet‐induced obesity and its metabolic sequelae. SYNOPSIS: Ceramide‐induced mitochondrial fission drives diet‐induced obesity and its metabolic sequelae. Here, a small molecule targeting endocytic trafficking was found to block mitochondrial fission and reverse high fat diet‐induced obesity and metabolic dysfunction in mice. The sphingolipid analog SH‐BC‐893 rapidly and robustly blocked ceramide‐induced mitochondrial fission by inhibiting ARF6‐dependent recycling and PIKfyve‐dependent lysosomal trafficking. Within 4 h of oral administration, SH‐BC‐893 corrected mitochondrial morphology and/or dysfunction in the liver, brain, and white adipose tissue of mice with high fat diet‐induced obesity. SH‐BC‐893 acutely re‐sensitized obese mice to leptin by reversing both hyperleptinemia and mitochondrial fragmentation in the hypothalamus, reducing food intake. Intermittent oral dosing with SH‐BC‐893 was well tolerated and normalized body weight, improved glucose handling, and resolved hepatic steatosis despite continued consumption of a high fat diet. Abstract : Ceramide‐induced mitochondrial fission drives diet‐induced obesity and its metabolic sequelae. Here, a small molecule targeting endocytic trafficking was found to block mitochondrial fission and reverse high fat diet‐induced obesity and metabolic dysfunction in mice.